Ringkasan Penelitian Kebutuhan Jabatan Fungsional Di Lingkungan Kementerian Perhubungan - Kuswati, Atik S (Warta Penelitian Perhubungan, 2010)
Policies and strategies fur Jmman rewurce derelopment in tranSfX»1ation ~kior is une of effurt to enhanceEerVices. Therefore, generate quality human resources and professional. is needed in aarmiance with theirfu:nctiona1 fXJSitions. Balancing quality and quantity of lmman resources with advance tranSJXJrl technologiesare exprted that transrxJrlation grnls will. re more sucressfa1 as 'lIBll as CXJr11¢e lXJth within and other amtries.Aavrding to improving transp:Jrlation sifthJ rxJlicy is net:ES.'m1j to cklxdap fafhJ audit amcept in prerentioneJjUrts to reduce tk incidence and accidents. Related tk mse is needed functional. fXJSitions as a sup;rvifm/insp?Cfor/auditor of each f£dmical. institution in ministnj of transp:Jrlation !£Cior (diredorale genem1. land trans]XJrl, mil'UXlljS, f£ll and air). Sup?YViror assi.gned to guarantee tk jaslbilittj of transp:Jrlation foci1itX!s indudingritk analysis of ead1 violation of eligibility requirements.Functional. ~J standards is necessary b:cauf£ it is a CUfXlbility that is lxlsed on knowledge, skills andgcxxl attitude whidi refers to tk peformance required This matter is explained in tk study of tk nea:ssity offuncional position by research and developmen of ministry of transport on 2009.